DIRECTIONS OF DEVELOPMENT OF STATE BUDGET CONTROL (American Journal of Interdisciplinary Research and Development, 2023)
In the article is discussed the reforms in the system of state budget control of Uzbekistan and aspects of its development. The main attention is paid to promising areas of budgetary control and the need to improve it, specific features of the legal and methodological support of budgetary control are disclosed.